Super-resolution RNA imaging using a rhodamine-binding aptamer with fast exchange kinetics - Sünbül, Murat; Lackner, Jens; Martin, Annabell; Englert, Daniel; Hacene, Benjamin; Grün, Franziska; Nienhaus, Karin; Nienhaus, G. Ulrich; Jäschke, Andres (Nature biotechnology, 2021)
Overcoming limitations of previous fluorescent light-up RNA aptamers for super-resolution imaging, we present RhoBAST, an aptamer that binds a fluorogenic rhodamine dye with fast association and dissociation kinetics. Its intermittent fluorescence emission enables single-molecule localization microscopy with a resolution not limited by photobleaching. We use RhoBAST to image subcellular structures of RNA in live and fixed cells with about 10-nm localization precision and a high signal-to-noise ratio.
Das PDF enthält zusätzlich einen Anhang von 8 Seiten
Gesehen am 26.02.2021